2014
DOI: 10.1002/jor.22715
|View full text |Cite
|
Sign up to set email alerts
|

Low-magnitude high-frequency vibration enhances gene expression related to callus formation, mineralization and remodeling during osteoporotic fracture healing in rats

Abstract: Low magnitude high frequency vibration (LMHFV) has been shown to improve anabolic and osteogenic responses in osteoporotic intact bones and during osteoporotic fracture healing; however, the molecular response of LMHFV during osteoporotic fracture healing has not been investigated. It was hypothesized that LMHFV could enhance osteoporotic fracture healing by regulating the expression of genes related to chondrogenesis (Col-2), osteogenesis (Col-1) and remodeling (receptor activator for nuclear factor-k B ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 28 publications
4
74
0
Order By: Relevance
“…Ten (Butezloff et al, 2015;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wei et al, 2016) of the nineteen studies adopt a 20 min/d treatment, four (Bilgin et al, 2017;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010) In this review, vibration regimes with a magnitude lower than 1 ×g were regarded as LMHFV and those with a magnitude greater than 1 ×g were regarded as HMHFV (high magnitude high frequency vibration). Six (Butezloff et al, 2015;Komrakova et al, 2016;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010;Usui et al, 1989) of the included studies use HMHFV and twelve (Bilgin et al, 2017;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Gao et al, 2016;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wolf et al, 2001) adopt LMHFV. One study uses both LMHFV and HMHFV (Uchida et al, 2017).…”
Section: Search Criteriamentioning
confidence: 98%
See 4 more Smart Citations
“…Ten (Butezloff et al, 2015;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wei et al, 2016) of the nineteen studies adopt a 20 min/d treatment, four (Bilgin et al, 2017;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010) In this review, vibration regimes with a magnitude lower than 1 ×g were regarded as LMHFV and those with a magnitude greater than 1 ×g were regarded as HMHFV (high magnitude high frequency vibration). Six (Butezloff et al, 2015;Komrakova et al, 2016;Komrakova et al, 2013;Stuermer et al, 2014;Stuermer et al, 2010;Usui et al, 1989) of the included studies use HMHFV and twelve (Bilgin et al, 2017;Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Gao et al, 2016;Leung et al, 2009;Shi et al, 2010;Wehrle et al, 2015;Wehrle et al, 2014;Wolf et al, 2001) adopt LMHFV. One study uses both LMHFV and HMHFV (Uchida et al, 2017).…”
Section: Search Criteriamentioning
confidence: 98%
“…Exclusion criteria were: 1) non-English-language papers; 2) not vibration treatment-related; 3) not Cheung et al, 2012;Chow et al, 2011;Chung et al, 2014;Gao et al, 2016;Komrakova et al, 2016;Komrakova et al, 2013;Leung et al, 2009;Shi et al, 2010;Stuermer et al, 2014;Stuermer et al, 2010;Uchida et al, 2017;Wei et al, 2016), two mouse studies (Wehrle et al, 2015;Wehrle et al, 2014), one sheep study (Wolf et al, 2001) and one rabbit study (Usui et al, 1989). No clinical study was found, based on our search criteria on publications prior to the 12 th March 2017.…”
Section: Search Criteriamentioning
confidence: 99%
See 3 more Smart Citations